Tissue distribution and integrated pharmacokinetic properties of major effective constituents of oral Gegen-Qinlian decoction in mice - Lu, Jing-Ze; Hong, Dan-Dan; Ye, Dan; Mu, Sheng; Shi, Rong; Song, Yu; Feng, Chu; Ma, Bing-Liang (Frontiers in Pharmacology, 2022)
Gegen-Qinlian decoction (GQD) is a classic traditional Chinese medicine (TCM) formula. GQD is effective against colon or liver-related diseases including ulcerative colitis, non-alcoholic fatty liver, and type 2 diabetes. In this study, a liquid chromatography-tandem mass spectrometry method was developed, validated, and then applied to reveal the tissue distribution and integrated pharmacokinetic properties of major effective constituents of oral GQD in mice. The established method was quick, sensitive, and accurate enough to analyze GQD constituents in plasma and tissue homogenate samples quantitatively. According to their concentrations in the portal vein, systemic circulation, liver and colon samples of the mice after oral administration of GQD, the concentration-time curves of the constituents were respectively plotted. The results showed that daidzein, baicalin, and baicalein had relatively high exposure levels in the livers, while puerarin, berberine, epiberberine, coptisine, palmatine, jatrorrhizine, magnoflorine, glycyrrhizic acid, and glycyrrhetinic acid were enriched in the colons. Given that these constituents have significant biological activity, they could be regarded as the major effective constituents of GQD in treating colon or liver-related diseases, respectively. In addition, the integrated pharmacokinetic properties of GQD were studied. The GQD “integrated constituent” reached peak concentration at 4.0 h in the portal vein, the systemic circulation, the livers, and the colons, with half-lives of 1.5-4.1 h and mean retention time of 4.5-6.3 h, respectively. Furthermore, the concentration of the GQD “integrated constituent” in the colons was approximately 10 times higher than that in the livers, both of which were much higher than that in the systemic circulation, indicating its accumulation in these tissues, especially in the colons. In conclusion, the tissue distribution and integrated pharmacokinetic properties of oral GQD were revealed in the study. The results of the tissue distribution study would contribute to identifying the major target tissues and effective constituents of GQD, while the results of the integrated pharmacokinetic study would help to explain the pharmacokinetic properties of oral GQD as a whole.